Audit of Blood Transfusion in Pediatric Unit of a Selected Private Medical College Hospital - Khan, Md. Mahbub Ul Karim; Hassan, Amirul; Shahnaz, Shoyela; Salahuddin, AKM (Medicine Today, 2012)
Medicine Today 2011 Volume 23 Number 01 Page 1-4 DOI: http://dx.doi.org/10.3329/medtoday.v23i1.11936